The Effect of Vitamin C Addition on the Antibacterial Activity of Pseudomonas aeruginosa in the Ethyl Acetate Fraction of Green Tea Leaves - Rayes, Norina Shaumy Putri; Permatasai, Lina; Mukhlshah, Neneng Rachmalia Izzatul; Octora, Metta; Arnawati, Ida Ayu; Jannah, Fathul (Jurnal Biologi Tropis, 2025)
Pseudomonas aeruginosais a major antibiotic-resistant pathogen frequently associated with hospital-acquired infections posing significant treatment challenges. This study aimed to evaluate the antibacterial activity of the ethyl acetate fraction of green tea (Camellia sinensis L.) enriched with vitamin C against Pseudomonas aeruginosa. The ethyl acetate fraction obtained from 96% ethanol maceration was tested at concentrations of 12,5-200 mg/mL both with and without vitamin C using the disk diffusion method and compared to aztreonam as a positive control. Results showed that vitamin C enrichment increased the inhibition zone from 12,5 mm to 13,8 mm at 200 mg/mL, while aztreonam produced the largest inhibition zone at 20,17 mm. The vitamin C-enriched formulation also maintened antibacterical activity more effectively over a 5-15 day storage period. Vitamin C is believed to stabilize the primary antimicrobial compound epigallocatechin gallate (EGCG) by preventing its oxidation. These findings support the potential of vitamin C-enriched green tea extract as an adjunctive therapy against Pseudomonas aeruginosa infections. Further development of topical or systemic formulations is recommended for managing resistant bacterial infections.